Autologous stem cell transplantation in patient with diffuse systemic sclerosis - A. Lo Monaco; F. Lanza; M. Dabusti; M. Padovan; R. La Corte; G. Castoldi; F. Trotta (PAGEPress Publications, 2002)
Systemic Sclerosis (SSc) is a systemic disease of unknown etiology presenting with disseminated skin thickening and fibrotic impairment of various organs including lung and kidney. According to the rate and degree of skin involvement, SSc can be classified in a limited and a diffuse form, the latter showing a severe and progressive lung involvement, which is responsible for its high related morbidity and mortality along with resistance to standard therapeutic protocols. High dose chemotherapy, followed by autologous stem cell transplantation, is a standard therapeutic regimen for haematological diseases: re-infusion of mobilised peripheral blood progenitor cells overcomes the myeloablative effect of super-maximal eradicative doses of chemotherapeutic agents. Recently, this therapeutic approach has been applied in some cases of resistant SSc and, albeit the low number of cases, it has been proven effective in early diagnosed and rapidly progressive forms of the disease showing a clinical improvement and an instrumentally detectable decrease of fibrosis extent. We report the case of a young woman affected by diffuse SSc with a rapid progression of clinical signs and instrumentally detectable lesions who underwent a conditioning regimen with fludarabine, cyclophosphamide and anti-thimoglobulines followed by re-infusion of autologous peripheral blood stem cells. Two years after transplantation a clinical and instrumental evidence of treatment was observed, with good control of disease evolution. The only sign of disease resumption was a slow worsening of skin involvement.